Discarded cigarette butts as overlooked reservoirs and amplifiers of antibiotic resistance genes and pathogens in urban green spaces - Jia-Yang Xu; Yi-Tian Yu; Shuai Du; Luo-Qin Shen; Qi Zhang; Haifeng Qian; Tian-Gui Cai; Yi-Fei Wang; Jun Zhao; Hong-Zhe Li; Chengdong Zhang; Dong Zhu (Proceedings of the National Academy of Sciences, 2025)
Cigarette butts are widely discarded in urban green spaces, yet their microbial health risks remain poorly understood. In a nationwide survey across China, we investigated the presence, sources, health risks, and drivers of antibiotic resistance genes (ARGs) and potential pathogens in discarded cigarette butts. Shotgun metagenomic and full-length 16S ribosomal rRNA (rRNA) sequencing revealed that cigarette butts harbored significantly higher abundances of ARGs and bacterial pathogens than plant litter or soil. Health risk assessment further showed that cigarette butts carried ARGs with greater mobility, clinical relevance, and pathogenic potential. Genomic analyses highlighted enrichment of ARG-carrying pathogens, particularly Enterobacteriaceae and Pseudomonas , with mobile genetic elements and oxidative stress responses as key contributors. Functional assays, including plasmid transfer, transcriptomic profiling, and single-cell Raman spectroscopy, demonstrated that cigarette butts promoted horizontal gene transfer and upregulated key ARGs (e.g., mexE , mexF , cfrC ) under stress conditions. Scanning electron microscopy confirmed biofilm formation on cigarette fibers, supporting enhanced bacterial persistence. Source-tracking analyses identified both human oral and environmental sources of the enriched ARGs and pathogens in cigarette butts. Finally, socioeconomic factors such as lower gross domestic product (GDP), reduced education, and poor sanitation were strongly associated with elevated ARG and pathogen risks. Collectively, our findings identify cigarette butts as overlooked yet potent vectors of ARG and pathogen dissemination in urban green spaces, underscoring the need for targeted interventions within a One Health framework.